Analisis Faktor- Faktor yang Mempengaruhi Kinerja Pegawai Pada SMP Negeri 2 Pangkalan Susu - zea zea; Syaiful Bahri; Leylia Khairani (CERED Indonesia Institute, 2020)
The purpose of this study was to analyze and determine the influence of organizational culture, job satisfaction and leadership style on employee performance at SMP Negeri 2 Pangkalan Susu. This study uses a quantitative associative approach with data collection techniques through literature study and questionnaires. The population and research sample were all staff and teachers at SMP Negeri 2 Pangkalan Susu totaling 30 employees. This research uses validity test, reliability test, classic assumption test, multiple linear regression test and hypothesis testing using the SPSS program. The results showed that: (1) partially organizational culture has a positive and significant effect on employee performance at SMP Negeri 2 Pangkalan Susu; (2) partially job satisfaction has a positive and significant effect on the performance of employees of SMP Negeri 2 Pangkalan Susu; (3) partially the leadership style has a positive and significant effect on the performance of the employees of SMP Negeri 2 Pangkalan Susu; (4) simultaneously organizational culture, job satisfaction and leadership style have a significant effect on the performance of employees of SMP Negeri 2 Pangkalan Susu.